Additive manufacturing and mechanical characterization of sinusoidal-based lattice structures: a numerical and experimental approach - Gómez-Castañeda, M.; Cuan-Urquizo, E.; Giraldo-Betancur, A. L.; Félix-Martínez, C.; Gómez-Ortega, A.; Alvarado-Orozco, J. M. (Progress in additive manufacturing, 2024)
The design and manufacturability of structured materials have been accelerated due to the advances in additive manufacturing (AM) technologies. The synthesis of structures with tailored made properties demands a thorough characterization of the geometric parameters-effective properties relation. In order to bring alternatives to this subject, this work is focused on analyzing the relation between geometric parametrization (amplitude, thickness, and wavelength) and mechanical properties (elastic modulus and Poisson’s ratio) of two sinusoidal-based lattice structures, i.e., achiral and chiral, through a computational-and-experimental approach. The apparent Young’s modulus was characterized by Finite Element computation analysis and experimental measurements on tensile specimens fabricated via extrusion-based AM. A correlation between the relative density, Poisson’s ratio, and its topological-geometrical parameters was obtained and discussed. The mechanical characterization showed a coupled bending-dominated response of the constituent struts with a rotational deformation of the nodes for both structures. In addition, the achiral structure exhibits a higher auxetic behavior than the chiral structure by a factor of 2.41 in the lowest relation density configurations. Moreover, a contrast with other cell topologies is presented, where the achiral structure is 6.56% softer than a reported square structure compared at the same relative density. Finally, a discussion concerning the deviations between experimental and computational data results was presented in terms of the current limitations and defects of the additive manufacturing process (e.g., infill type, extruding temperature, nozzle geometry) of the tensile specimens.